Ag nanoparticle-decorated 2D/2D S-scheme g-C3N4/Bi2WO6 heterostructures for an efficient photocatalytic degradation of tetracycline. Issue 26 (14th June 2021) - Dou, Xincheng; Li, Qiaoqiao; Shi, Haifeng
Abstract : The 2D/2D S-scheme Ag–g-C3 N4 –Bi2 WO6 composite with efficient charge transfer, displayed a remarkable degradation activity of tetracycline under visible light irradiation. Abstract : As one of the largest pharmaceutical combinations used in therapeutic medicine and feed supplements, the problem of water pollution caused by antibiotics has been put in the spotlight. In this work, tetracycline hydrochloride (TC) was efficiently photocatalytically degraded over 2D/2D S-scheme Ag x –g-C3 N4 –Bi2 WO6 (A x C/B) photocatalysts, which were prepared using a simple hydrothermal method. Under visible-light irradiation, the TC degradation efficiency of A3C/B reached 81.4% in 60 min, which was 2.85 times and 1.52 times those of pure CN and pure BWO, respectively. The enhanced TC degradation performance of A3C/B was mainly due to the synergistic effect of the abundant active sites and efficient photo-generated carrier separation rate in the 2D/2D S-scheme system. In addition, Ag nanoparticles acted as cocatalysts, which would promote electron migration from the conduction band of CN by forming a Schottky barrier between CN and Ag. The main reactive species, superoxide radicals (˙O2 − ), hydroxyl radicals (˙OH) and holes (h + ), were all involved in the reaction, which was proved by a trapping experiment. In summary, this research showed that A3C/B was significant for TC degradation under visible-light illumination and provided a novel strategy for TC degradation of various S-scheme 2D/2D-like photocatalysts.